Giant Heterometallic [Mn36Ni4]0/2− and [Mn32Co8] “Loops-of-Loops-and-Supertetrahedra” Molecular Aggregates - Charalambous, Maria; Moushi, Eleni E.; Nguyen, Tu N.; Papatriantafyllopoulou, Constantina; Nastopoulos, Vassilios; Christou, George; Tasiopoulos, Anastasios J. (Frontiers in Chemistry, 2019)
We report the synthesis, crystal structures and magnetic properties of the giant heterometallic [Mn36Ni4]2-/0 (compounds 1, 2) / [Mn32Co8] (compound 3) ‘loops-of-loops-and-supertetrahedra’ molecular aggregates and of a [Mn2Ni6]2+ compound (cation of 4) that is structurally related with the cation co-crystallizing with the anion of 1. In particular, after the initial preparation and characterization of compound [Mn2Ni6(μ4-Ο)2(μ3-ΟH)3(μ3-Cl)3(O2CCH3)6(py)8]2+[Mn36Ni4(μ4-Ο)8(μ3-Ο)4(μ3-Cl)8Cl4(O2CCH3)26(pd)24(py)4]2- [1] we targeted the isolation of i) both the cationic and the anionic aggregates of 1 in a discrete form and ii) the Mn/Co analogue of [Mn36Ni4]2- aggregate. Our synthetic efforts towards these directions afforded the discrete [Mn36Ni4] ‘loops-of-loops-and-supertetrahedra’ aggregate [Mn36Ni4(μ4-Ο)8(μ3-Ο)4(μ3-Cl)8Cl2(O2CCH3)26(pd)24 (py)4(Η2Ο)2] [2], the heterometallic Mn/Co analogue [Mn32Co8(μ4-O)8(μ3-O)4(μ3-Cl)8Cl2(μ2-OCH2CH3)2(O2CCH3)28(pd)22(py)6] [3] and the discrete [Mn2Ni6]2+ cation [Mn2Ni6(μ4-Ο)2(μ3-ΟH)4(μ3-Cl)2(O2CCH3)6(py)8](ClO4)(OH) [4]. The structure of 1 consists of a mixed valence [MnIII28MnII8NiII4]2- molecular aggregate that contains two MnIII8NiII2 loops separated by two MnIII6MnII4 supertetrahedral units and a [MnIII2NiII6]2+ cation based on two [MnIIINiII3(μ4-O)(μ3-OH)1.5(μ3-Cl)1.5]4+ cubane sub-units connected through both mono- and tri-atomic bridges provided by the μ4-O2- and carboxylate anions. The structures of 2 – 4 are related to those of the compounds co-crystallized in 1 exhibiting however some differences that shall be discussed in detail in the manuscript. Magnetism studies revealed the presence of dominant ferromagnetic interactions in 1-3 that lead to large ground state spin (ST) values for the ‘loops-of-loops-and-supertetrahedra’ aggregates and antiferromagnetic exchange interactions in 4 that lead to a low (and possibly zero) ST value. In particular, dc and ac magnetic susceptibility studies revealed that the discrete [Mn36Ni4] aggregate exhibits a large ST value~ 26 but is not a new SMM. Interestingly, ac magnetic susceptibility studies of the [Mn32Co8] analogue revealed the appearance of an out-of-phase tail at low T indicating the existence of slow relaxation of the magnetization possibly due to the presence of the anisotropic Co2+ ions in this compound.